Unveiling Key Descriptors of Ionomer Materials for Enhanced Electrochemical CO2 Reduction - Jung, Wonsang; Shin, Sang-Hun; Park, Sejin; Chae, Younghyun; Lee, Ung; Cho, Hye Jin; Kim, Sungjun; Hwang, Yun Jeong; Lee, Jang Yong; Won, Da Hye (American Chemical Society, 2025)
Polymeric ionomers near the catalyst surface of CO2 reduction reaction (CO2RR) electrodes affect their efficiency; however, their multifaceted properties complicate structure-activity relationship elucidation. Here, we synthesized polycarbazole-based anion-exchange (QPC) ionomers bearing varying functionalized side chains to explore this relationship. Comprehensive analysis in physicochemical properties, electrochemical activity, and operando ATR-SEIRAS revealed that functional group modification significantly influenced the intrinsic ionomer properties, thereby affecting the Ag catalyst properties, microenvironments of interfacial water structures, and reaction kinetics of the protonation step for CO2RR and the hydrogen evolution reaction (HER). Notably, the QPC-trimethyl phosphonium (TMP) ionomer induced favorable interfacial water structures, having a high proportion of strong H-bonded water with low Stark tuning slopes, which inhibit HER and promote CO2RR. A high CO Faradaic efficiency (>90%) was maintained using QPC-TMP in a membrane electrode assembly, even under varying CO2 concentrations (100-15%) and elevated temperatures (28-72 degrees C). These findings suggest that the catalytic environment can be optimized by fine-tuning the ionomer structure, contributing to the advancement of high-performance CO2RR ionomers.